A Tropical Cyclone-Induced Ecological Regime Shift: Mangrove Forest Conversion to Mudflat in Everglades National Park (Florida, USA) - Osland, Michael J.; Feher, Laura C.; Anderson, Gordon H.; Vervaeke, William C.; Krauss, Ken W.; Whelan, Kevin R.T.; Balentine, Karen M.; Tiling-Range, Ginger; Smith, Thomas J.; Cahoon, Donald R. (Wetlands (Wilmington, N.C.), 2020)
The ecological effects of tropical cyclones on mangrove forests are diverse and highly location- and cyclone-dependent. Ecological resistance, resilience, and enhancement are terms that describe most mangrove forest responses to tropical cyclones. However, in the most extreme cases, tropical cyclones can trigger abrupt and irreversible ecological transformations (i.e., ecological regime shifts). Here, we examine a cyclone-induced ecological regime shift that occurred in Everglades National Park (USA), where forest mortality and peat collapse due to a powerful tropical cyclone (the 1935 Labor Day Hurricane) led to the conversion of mangrove forests to mudflats and an estimated elevation loss of approximately 75 cm. We investigated soil elevation change measured in these mangrove forests and adjacent mudflats during a twenty-year period [1998–2018] using Surface Elevation Table-Marker Horizon (SET-MH) methods. This period encompasses the effects of Hurricanes Wilma (2005) and Irma (2017). We also used historical sea-level rise rates and future sea-level rise scenarios to estimate surface elevation changes in the past (1930–1998) and to illustrate elevation gains needed for these ecosystems to adapt to future change. Collectively, our findings advance understanding of the long-term effects of cyclone-induced ecological regime shifts due to forest mortality, peat collapse, and conversion of mangrove forests to mudflats.